The beginnings of the prehistoric agriculture in the Russian far east - Kuzmin, Yaroslav V. (Documenta Praehistorica, 2013)
The current situation with studies of prehistoric plant cultivation in the Russian Far Eastis presented. A critical analysis of existing concepts and models of the oldest agriculture in this regionis also included. Reliable data allows us to conclude that humans in the southern Russian Far East(Primorye Province) began to cultivate millet atc.47004600 BP (c.36003400 calBC) in the contextof the early Zaisanovka cultural complex of the Late Neolithic. The most probable source area forprehistoric agriculture in the Russian Far East was neighbouring Northeast China (Manchuria).
Keywords: kulturne rastline; neolitik; poljedelstvo; Rusija; Sibirija